Why Do Teachers Dislike Educational Theory? - Bolesław Niemierko (Nauki o Wychowaniu, 2025)
Scientific theory holds a dual significance in education: substantive, as it provides learning content, and instrumental, as it explains the process of mastering it. In this second role, it becomes the subject of ongoing doubts, debates, trials, and fascinations. Educational theorists spare no effort in attempting to match the methodological rigor of the natural sciences, yet their achievements in this regard are often heavily questioned by practitioners. The author of the article examines these controversies within the unique context of Poland, a Central Eastern European country still affected by authoritarianism. In an increasingly globalized world, cultural differences between social functions and their executors are, in the author’s view, becoming more pronounced.